Does Operative Intervention Provide Early Pain Relief for Patients With Unilateral Sacral Fractures and Minimal or No Displacement?. Issue 12 (December 2019) - Tornetta, Paul; Lowe, Jason A.; Agel, Julie; Mullis, Brian H.; Jones, Clifford B.; Teague, David; Kempton, Laurence; Brown, Krista; Friess, Darin; Miller, Anna N.; Spitler, Clay A.; Kubiak, Erik; et al.
Abstract : Objectives: To compare pain after operative versus nonoperative pelvic ring injuries with unilateral sacral fractures. Design: Prospective, multicenter, observational. Setting: Sixteen trauma centers. Patients/Participants: Skeletally mature patients with pelvic ring injury and minimally displaced unilateral zone 1 or 2 sacral fractures and without anteroposterior compression injuries. Main Outcome Measurements: Pelvic displacement was documented on injury plain radiographs and computed tomography scans; a 10 point Visual Analog Scale (VAS) was used to evaluate pain was obtained in the anterior and posterior pelvic ring during the time of union (12 weeks). Results: One hundred ninety-four patients with unilateral sacral fractures displaced less than 5 mm, mean age of 38.7, and mean Injury Severity Score of 14.5 were included. Ninety-nine percent had lateral compression injuries, and 62% were in zone 1. Seventy-four percent were treated nonoperatively. Nonoperative patients had more zone 1 fractures (71%, P = 0.004). Nonoperative patients reported mean VAS 2.7 points higher in the posterior pelvis ( P = 0.01) and 1.9 points higher anteriorly ( P = 0.11) 24 hours after injury compared with patients treated operatively. After 3 months, nonoperative patients reported higher VAS scores than operative patients: 4.0 versus 2.9 posteriorly ( P = 0.019) and 3.2 versus 2.3 anteriorly ( P = 0.035). Conclusions: For sacrum fractures with minimal or no displacement, slight differences in the VAS were noted within 24 hours after injury or surgery, but limited differences were seen at 3 months for either operatively treated minimally or undisplaced sacrum fractures. It is unknown whether this represents clinical relevance. These differences were below the minimally important clinical difference for VAS scores for other orthopaedic conditions. Level of Evidence: Therapeutic Level II. See Instructions for Authors for a complete description of levels of evidence.